INDEKS PEMAKAIAN AIRTANAH DI KOTA YOGYAKARTA - Ahmad Cahyadi; Indra Agus Riyanto; Hendy Fatchurohman; Sigit Heru Murti Budi Santosa; Raras Endarto (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2020)
The rapid development of the city causes an increase in the amount of water that needed to support various activities. The Utilization of groundwater in large quantities causes negative impacts such as the decrease in groundwater level so that people are difficult to access groundwater. The aim of this study is to analyze the index of groundwater use which describe the condition of groundwater use in the city of Yogyakarta. The groundwater use index is calculated by dividing the total water demand and the availability of groundwater in the City of Yogyakarta. The result shows that in general groundwater use in the city of Yogyakarta is categorized in the safe enough classification (III). However, in the shallow groundwater use index there is one area with less safe classification (II) namely Kotagede District, and one area with unsafe classification (I) namely Umbulharjo District. The main factor which influence to the high index of shallow groundwater use is large population that causes high water domestic needs. This is reflected in the percentage of water domestic needs reaching 90.43%.Keywords: Groundwater, Index of Groundwater Use, Yogyakarta City Perkembangan kota yang pesat menyebabkan semakin banyak jumlah air yang dibutuhkan untuk menunjang berbagai kegiatan di dalamnya. Pemanfaatan airtanah dalam jumlah yang besar menyebabkan dampak negatif seperti penurunan muka airtanah, sehingga masyarakat sulit untuk mengakses airtanah tersebut. Penelitian ini bertujuan menganalisis indeks pemakaian airtanah yang diharapkan dapat menggambarkan kondisi penggunaan airtanah di Kota Yogyakarta. Indeks pemakaian airtanah dihitung dengan membagi total kebutuhan air dengan ketersediaan airtanah di Kota Yogyakarta. Hasil analisis menunjukkan bahwa secara umum pemakaian airtanah di Kota Yogyakarta masuk dalam klasifikasi cukup aman (III). Namun demikian pada indeks pemakaian airtanah dangkal terdapat satu wilayah dengan klasifikasi kurang aman yakni Kecamatan Kotagede, dan satu wilayah dengan klasifikasi tidak aman, yakni Kecamatan Umbulharjo. Faktor utama yang berpengaruh tingginya indeks pemakaian airtanah dangkal adalah jumlah penduduk yang sangat besar yang menyebabkan kebutuhan air domestik yang sangat tinggi. Hal tersebut tergambar dari nilai persentase kebutuhan domestik yang mencapai 90,43%Kata Kunci: Airtanah, Indeks Pemakaian Airtanah, Kota Yogyakarta